2021
DOI: 10.1515/ntrev-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of 3D-printed gellan gum/starch composite scaffold for Schwann cells growth

Abstract: Peripheral nerve injury has seriously affected patient’s health and life. Schwann cells play an important role in peripheral nerve regeneration. However, the effect of the current tissue engineered scaffolds for promoting Schwann cells growth is still not as good as that of autologous graft. In this study, new developed three-dimensional gellan gum/starch (GG/ST) scaffolds with various printing gap for Schwann cells growth were prepared by 3D printing technology. Various physiochemical characterizations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Compared with pure HA and GG, the cross-linked HEG still maintains good biocompatibility. 73,74 All in all, the CCK-8 test, live/dead assay, and DAPI/phalloidin staining show that the HEG based viscosupplements have good biocompatibility in the articular cavity environment, which presents great potential for intra-articular injection.…”
Section: Resultsmentioning
confidence: 96%
“…Compared with pure HA and GG, the cross-linked HEG still maintains good biocompatibility. 73,74 All in all, the CCK-8 test, live/dead assay, and DAPI/phalloidin staining show that the HEG based viscosupplements have good biocompatibility in the articular cavity environment, which presents great potential for intra-articular injection.…”
Section: Resultsmentioning
confidence: 96%
“…This modification strategy allowed the authors to obtain hydrogels with good mechanical and rheological properties and to print starch structures without the need for any additional heat treatment. In a different vein, pure starch was combined with gellan gum to formulate 3D-printed scaffolds with various printing gaps for seeding Schwann cells [ 148 ]. Results indicated that the printed constructs were stable, with adequate swelling ratios, and were non-cytotoxic toward the L929 fibroblast cell line.…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…GG dissolves in hot water assuming a “random coil” state and, when the temperature decreases, it self-organizes into a “double helix” structure, which is further stabilized by the presence of divalent cations [ 11 , 12 ]. GG and its derivatives have usually been employed as viscous enhancers [ 13 ] and in combination with other synthetic or natural polymers, such as starch [ 14 ], chitosan [ 15 ], methacrylated gelatin [ 16 ] and alginate [ 17 ], for regenerative medicine. As a biomaterial ink, it has many advantages over other hydrogels, including a high gelling efficiency at physiological temperature and a reasonable production cost [ 18 ].…”
Section: Introductionmentioning
confidence: 99%